Designing A Blockchain Layer in Smart Grid Edge Iot Devices to Enhance Data Security - Iindombo, Sakaria Amakali. (Namibia University of Science and Technology, 2024)
A smart grid is an electricity network that uses digital technologies to minimize cost and maximize system scalability to meet the demands of end users. It is a bidirectional system that enables various renewable sources to produce clean energy to the grid, unlike the conventional grid. The smart grid is made up of interconnected edge IoT devices to provide real-time data and monitor the network in enabling data driven decision-making. Studies indicate that by 2025, there will be 75.44 billion connected devices due to the rise in the deployment of edge IoT devices. Given the current increase of edge IoT devices, data security concerns have arisen, exposing the grid to a wide range of attacks. Most of the edge IoT devices are deployed geographically dispersed, which makes management challenging. They are also built with limited system capabilities and lack of security considerations in their design. This study focused on the three most severe threats against smart grid edge IoT devices which are denial-of-service attacks, unsecure protocols, and firmware exploits as identified by a systematic literature review. The study aimed to design a blockchain layer that could enhance data security in edge IoT devices, using purified lightweight security protocols namely, ACL’s, SSL/TLS and RBAC. Hyperledger Fabric blockchain layer was selected for its suitability in distributed edge computing due to its modular architecture, robust security features, and scalability. The study used a systematic literature review to investigate threats, analyze current deployment of blockchain layers, and to select lightweight security protocols to enhance the Hyperledger Fabric. An experiment was conducted by simulating the effects of attacks on the edge IoT smart grid, both before and after lightweight security protocols were applied on the blockchain layer. In each experiment, three types of attacks were conducted: denial-of-service, packet sniffing and firmware exploit. The results of the experiments show that without lightweight security protocols on the blockchain layer increased latency, packet loss, user credentials being transmitted in plaintext and success of firmware exploitation is experienced. Results from experiments after lightweight security protocols were applied on the blockchain layer, show a reduction of malicious traffic success, encrypted user credentials, and unsuccessful firmware exploit. As a result, the study recommends employing lightweight security protocols in the blockchain to ensure data integrity, confidentiality and availability. This will be useful to reduce computational burden, allowing edge IoT devices to operate more efficiently. In turn, this study iii provides valuable insights for electricity service providers on effectively managing edge IoT devices in the smart grid and to promote renewable energy adoption. Ultimately, safeguarding the smart grid's data security to ensure human safety.